Synthesis and reception of prostaglandins in corpora lutea of domestic cat and lynx. Issue 2 (August 2016) - Zschockelt, Lina; Amelkina, Olga; Siemieniuch, Marta J; Kowalewski, Mariusz P; Dehnhard, Martin; Jewgenow, Katarina; Braun, Beate C
Abstract : Felids show different reproductive strategies related to the luteal phase. Domestic cats exhibit a seasonal polyoestrus and ovulation is followed by formation of corpora lutea (CL). Pregnant and non-pregnant cycles are reflected by diverging plasma progesterone (P4) profiles. Eurasian and Iberian lynxes show a seasonal monooestrus, in which physiologically persistent CL (perCL) support constantly elevated plasma P4 levels. Prostaglandins (PGs) represent key regulators of reproduction, and we aimed to characterise PG synthesis in feline CL to identify their contribution to the luteal lifespan. We assessed mRNA and protein expression of PG synthases ( PTGS2/COX2, PTGES, PGFS/AKR1C3) and PG receptors ( PTGER2, PTGER4, PTGFR), and intra-luteal levels of PGE2 and PGF2α . Therefore, CL of pregnant (pre-implantation, post-implantation, regression stages) and non-pregnant (formation, development/maintenance, early regression, late regression stages) domestic cats, and prooestrous Eurasian (perCL, pre-mating) and metoestrous Iberian (perCL, freshCL, post-mating) lynxes were investigated. Expression of PTGS2/COX2, PTGES and PTGER4 was independent of the luteal stage in the investigated species. High levels of luteotrophic PGE2 in perCL might be associated with persistence of luteal function in lynxes. Signals for PGFS/AKR1C3 expression were weak in mid and late luteal stages of cats but were absent in lynxes, concomitant with low PGF2α levels in these species. Thus, regulation of CL regression by luteal PGF2α seems negligible. In contrast, expression of PTGFR was evident in nearly all investigated CL of cat and lynxes, implying that luteal regression, e.g. at the end of pregnancy, is triggered by extra-luteal PGF2α .